Indirect Effects of the Herbicide Glyphosate on Plant, Animal and Human Health Through its Effects on Microbial Communities - van Bruggen, A. H. C.; Finckh, M. R.; He, M.; Ritsema, C. J.; Harkes, P.; Knuth, D.; Geissen, V. (Frontiers in Environmental Science, 2021)
The herbicide glyphosate interferes with the shikimate pathway in plants and in major groups of microorganisms impeding the production of aromatic amino acids. Glyphosate application on plants results in a slow death, accelerated by reduced resistance to root pathogens. Extensive glyphosate use has resulted in increasing residues in soil and waterways. Although direct glyphosate effects on animals are limited, major concerns have arisen about indirect harmful side effects. In this paper, we focus on indirect effects of sublethal concentrations of glyphosate on plant, animal and human health due to shifts in microbial community compositions in successive habitats. Research results of glyphosate effects on microbial communities in soil, rhizosphere and animal guts have been contradictory due to the different integration levels studied. Most glyphosate studies have tested short-term treatment effects on microbial biomass or general community composition at higher taxonomic levels in soil, rhizosphere or animal intestinal tracts, and found little effect. More detailed studies showed reductions in specific genera or species as well as biological processes after glyphosate application. Plant growth promoting rhizobacteria and beneficial intestinal bacteria often are negatively affected, while pathogenic bacteria and fungi are enhanced. Such shifts in microbial community composition have been implicated in enhanced susceptibility of plants to Fusarium and Rhizoctonia, of birds and mammals to toxic Clostridium and Salmonella species, and of bees to Serratia and Deformed Wing Virus. In animals and humans, glyphosate exposure and concentrations in urine have been associated with intestinal diseases and neurological as well as endocrine problems, but cause-effect relationships need to be determined in more detail. Nevertheless, outbreaks of several animal and plant diseases have been related to glyphosate accumulation in the environment. Long-term glyphosate effects have been underreported, and new standards will be needed for residues in plant and animal products and the environment.